Pharmacokinetic Profiling and Molecular Docking of Carvacrol and Structural Analogs: Targeting Quorum Sensing Proteins to Disrupt Biofilm-Mediated Antimicrobial Resistance in Multidrug-Resistant Bacterial Pathogen - Muhammed Roshan K K (International Journal of Biochemistry and Biomolecule Research, 2025)
Antibiotic resistance, particularly in Pseudomonas aeruginosa, has become a major global health threat, exacerbated by the organism's ability to form biofilms and regulate virulence through quorum sensing (QS). The LuxR and LasR receptors are key regulators in this process, influencing both pathogenicity and antibiotic resistance. This study investigates potential QS inhibitors targeting these receptors as a strategy to mitigate antibiotic resistance. The primary objective was to identify novel ligands that can disrupt QS signaling in P. aeruginosa. Computational techniques, including molecular docking, pharmacological screening, and post-docking analysis, were employed to identify and evaluate potential QS inhibitors. A selection of ligands was docked into the LuxR and LasR receptor binding pockets to assess binding affinities. Compounds such as homosalate, 2,2'-biphenol, and 2-methyl-4-oxo-1,4-dihydroquinolin-3-olate displayed strong binding affinities of -9.4 kcal/mol, -9.4 kcal/mol, and -8.8 kcal/mol, respectively. Post-docking analysis revealed significant interactions, including hydrogen bonds, hydrophobic interactions, and electrostatic forces, suggesting a robust binding mechanism. Pharmacological evaluations of these compounds indicated favorable properties, such as appropriate molecular weight, solubility, and lipophilicity, making them promising candidates for further development. The results indicate that these compounds could serve as effective QS inhibitors, potentially disrupting P. aeruginosa’s ability to form biofilms and regulate virulence, thereby restoring antibiotic efficacy. But we still need experiments to prove these findings. The study's limitations include the need for in vitro and in vivo testing, as well as optimization of the compounds for improved pharmacokinetic profiles. This research highlights the potential of QS inhibition as an alternative strategy for combating antibiotic resistance, with promising future perspectives for drug development.
Keywords: LasR; LuxR; MDR; Quorum sensing; antibiotic resistance; carvacrol; molecular docking